In Vitro Antimicrobial Sensitivity of Escherichia coli Isolated from Clinical Sources (Journal of Bangladesh Academy of Sciences, 2010)
A study of antimicrobial sensitivity of Escherichia coli (E. coli) isolated from clinical sourcesof different diagnostic centers of Dhaka, Bangladesh was carried out to facilitate the choice of drugin the management of E. coli induced symptoms. Very low sensitivity of E. coli towards ampicillin(4%), aztreonam (4%), cloxacillin (5%), nalidixic acid (5%), ciprofloxacin (7.5%), ceftriaxone(12.5%), doxycycline (12.5%), ceftazidime (16.25%), co-trimoxazole (20%), chloramphenicol(22.51%), tetracycline (25%), and netilmicin (35%) was observed. Higher sensitivity pattern wasobserved for gentamicin (56%) and only imipenem (95%) showed sensitivity pattern possiblysusceptible enough to consider for the management of E. coli induced cases in the area under study.The low sensitivity to different antimicrobial could be attributed to their prevailing usage and abusein the area under study.Key words: E. coli; Antimicrobial sensitivity; Clinical isolatesDOI: 10.3329/jbas.v34i1.5497Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 99-101, 2010